Efficient Production of a Bioactive Bevacizumab Monoclonal Antibody Using the 2A Self-cleavage Peptide in Transgenic Rice Callus - Chen, Lei; Yang, Xiaoyu; Luo, Da; Yu, Weichang (Frontiers in Plant Science, 2016)
Bevacizumab, a humanized monoclonal antibody (mAb) targeting to the vascular endothelial growth factor (VEGF), has been widely used in clinical practice for the treatment of multiple cancers. Bevacizumab was mostly produced by the mammalian cell expression system. We here reported the first plant-derived Bevacizumab by using transgenic rice callus as an alternative gene expression system. Codon-optimized Bevacizumab light chain (BLC) and heavy chain (BHC) genes were designed, synthesized as a polyprotein with a 2A self-cleavage linker peptide from the Foot-and-mouth disease virus (FMDV), cloned into a plant binary vector under a constitutive maize ubiquitin promoter, and transformed into rice nuclear genome through Agrobacterium-mediated transformation. Southern blot and western blot analyses confirmed the integration and expression of BLC and BHC genes in transgenic rice callus. Enzyme linked immunosorbent assay (ELISA) analysis indicated that the rice-derived Bevacizumab mAb was biologically active and the recombinant mAb was expressed at high levels (160.7-242.8 mg kg-1FW) in transgenic rice callus. The mAb was purified by using protein A affinity chromatography and the purified antibody was tested for its binding affinity with its target hVEGF antigen by ELISA. Rice callus produced Bevacizumab and a commercial Bevacizumab (Avastin) were shown to have similar binding affinity to hVEGF. These results indicated that rice callus produced Bevacizumab could have similar biological activity and might potentially be used as a cost-effective biosimilar molecule in future cancer treatment.